HIV Vertical Transmission Does Not Differ When Using Protein Inhibitor or Integrase Inhibitor Antiretrovirals [17OP]. (May 2018) - Gomez, Luis M.; Sublette, Nina; Wang, Jenny Q.; Samson, Fernand; Tate, Danielle L.
Abstract : INTRODUCTION: HIV vertical transmission is reduced from 25% (baseline) to <2% with combined-antiretroviral therapy (cART) when the viral load (VL) near delivery is <1, 000 copies/mL. For many years, the standard cART in pregnancy included 2 nucleoside reverse transcriptase inhibitors and 1 protease inhibitor (PI). Recently, integrase strand transfer inhibitors (INSTI) have been approved for use in pregnancy as an alternative to PI. We sought to compare the rate of HIV vertical transmission in women receiving PI- to those receiving INSTI-based cART. METHODS: This was a prospective cohort study of pregnant HIV-infected women who received care in an obstetric infectious disease clinic during 2010–2016. Women were included if they had at least 2 VL (before and after intervention) obtained during pregnancy. Our primary outcome was the rate of vertical transmission. Secondary outcomes included the rate of VL<1, 000 copies/mL and undetectable VL near delivery. RESULTS: 156 women received PI-based cART and 98 INSTI-based cART. The rate of vertical transmission was 0.6% (1/156) in the PI-group and 3% (3/98) in the INSTI-group ( P =.32). After adjusting for confounders, the rate of VL<1, 000 copies/mL near delivery was similar among both groups: PI=77.6% (121/156), and INSTI=81.2% (80/98); P =.37. More women in the INSTI-group had undetectable VL near delivery, 75.5% (74/98) vs PI-group, 46.1% (72/156); P =.001. CONCLUSION: HIV-infected pregnant women treated with PI- or INSTI-based cART had statistically comparable rates of vertical transmission. Both treatment groups achieved similar rates of VL<1, 000 copies/mL near delivery and appeared equivalently efficacious to treat HIV-infected women in pregnancy.